Investigating Public Participation as a Strategy to Improve Drinking Water Utilities' Financial Security - Kohn, Amanda. (2018)
Abstract: Communities across the United States are at risk because drinking water utilities are unable to invest in critical infrastructure. Many utilities rely on rates to cover costs, but rates have not increased to match utilities' growing needs. The aim of this study is to examine how community engagement can be used a tool to strengthen utilities' financial security. A national survey of drinking water professionals was conducted to delineate utilities' public participation and infrastructure investment practices. Many utilities are conducting community engagement and agreed that it strengthens infrastructure investment. The most widely practiced engagement techniques are one-way communications that fail to share decision making power. The survey also indicated that public perception is closely linked to the ability to change rates. The results suggest community engagement can be a viable strategy to increase public support for rate changes and thus strengthen utilities' financial capacity to invest in infrastructure.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Eric Kemp-Benedict.; Keywords: Water resources management, Public administration, and Public policy.